Criminal Legal Policy On Insults Against The President And Vice President Post Constitutional Court Ruling Number 7/Puu-Xxi/2023 - Dian Adriawan Dg Tawang; Rini Purwaningsih (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research discusses criminal law policies related to insulting the President and Vice President in Indonesia after the Constitutional Court (MK) decision. Previously, Articles 134, 136 bis, and 137 of the Criminal Code regulated criminal acts of insulting the President and Vice President, but these articles were abolished through Constitutional Court Decision Number 7/PUU-XXI/2023 on the grounds that they conflicted with the freedom of expression guaranteed by the 1945 Constitution . This decision raises a dilemma between protecting the dignity of high-ranking state officials and freedom of expression. Along with the introduction of the new Criminal Code in January 2023 through Law Number 1 of 2023 following the decision, there are legislative efforts to introduce new insult articles that are more in line with human rights principles. This research highlights the legal and social implications of these policy changes, including their potential impact on press freedom and political dynamics. Analysis of the Constitutional Court's decision according to the new Criminal Code shows the need to balance between protecting the presidential institution and maintaining the space for freedom of expression in Indonesia.